Atypical presentation of first-episode psychosis: pedal edema in a patient with autism - Parikh, Parinda; Bhatta, Aatish Dutta; Alphonse, Alisha Arul; Kays, Jeremy; Singh, Shaurya Kumar; Suthar, Himani J.; Shukla, Arnesh; Pansuriya, Parthiv Chunilal; Buddhavarapu, Mahiya; Chandra, Arushi Kaushik; Gellert, Zoe; Oza, Mina (International Journal Of Community Medicine And Public Health, 2025)
First episode psychosis (FEP) in adolescents with autism spectrum disorder (ASD) presents unique diagnostic and management challenges due to overlapping symptomatology. Physical findings such as pedal edema are uncommon in early psychosis and warrant careful evaluation, particularly prior to initiating antipsychotic treatment. We report a case of a 16-year-old male with ASD who presented with FEP characterized by catatonia, behavioral rigidity, reduced sleep, and social withdrawal. On examination, he exhibited bilateral pitting pedal edema without evidence of systemic or pharmacologic causes. Collateral history revealed prolonged standing behavior due to motor immobility (catatonia) and behavioral abnormalities. Laboratory and imaging investigations were unremarkable. The edema was attributed to dependent fluid accumulation secondary to catatonic posturing. The patient was initiated on long-acting injectable aripiprazole and supportive measures, including compression therapy and hydration, with close monitoring. This case highlights the importance of distinguishing behavioral and physical manifestations of psychosis from baseline ASD traits and other medical conditions. Pedal edema occurring before antipsychotic treatment is uncommon and warrants a thorough evaluation to prevent inadvertently attributing it to medication side effects. Catatonia-related posturing may be an underrecognized contributor to dependent edema in this population. This case highlights the challenges of diagnosing psychosis in autism, where symptoms may overlap with baseline traits. Catatonia presenting as prolonged standing might result in pedal edema. Comprehensive history and multidisciplinary assessment enables accurate diagnosis and treatment, emphasizing the need for careful monitoring in this population.